ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia 2013-2015) - Lucky Aryo Prabowo, 13.05.52.0167; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2017)
This study aims to analyze the Influence of Company Size, Business Risk, Corporate Growth, Asset Structure, Profitability, and Capital Expenditure on Capital Structure in Manufacturing Companies listed on Indonesia Stock Exchange. The sample in this research is 280, sample selection is done by purposive sampling method. The analysis technique used multiple linear regression analysis. The result of analysis shows that Business Risk variable, and Asset Structure have significant effect to capital structure while Corporate Size variable, Corporate Growth, Profitability, and Capital Expenditure do not influence to capital structure at Manufacturing Company listed in Indonesia Stock Exchange.Keywords: Company Size, Business Risk, Corporate Growth, Asset Structure, Profitability, and Capital Expenditure